Difference between revisions of "009B Sample Midterm 1, Problem 5"

From Math Wiki
Jump to navigation Jump to search
Line 10: Line 10:
 
|Recall:
 
|Recall:
 
|-
 
|-
|'''1.''' The height of each rectangle in the left-hand Riemann sum is given by choosing the left endpoint of the interval.
+
|
 +
::'''1.''' The height of each rectangle in the left-hand Riemann sum is given by choosing the left endpoint of the interval.
 
|-
 
|-
|'''2.''' The height of each rectangle in the right-hand Riemann sum is given by choosing the right endpoint of the interval.
+
|
 +
::'''2.''' The height of each rectangle in the right-hand Riemann sum is given by choosing the right endpoint of the interval.
 
|-
 
|-
|'''3.''' See the page on [[Riemann_Sums|'''Riemann Sums''']] for more information.
+
|
 +
::'''3.''' See the page on [[Riemann_Sums|'''Riemann Sums''']] for more information.
 
|}
 
|}
  
Line 23: Line 26:
 
!Step 1:    
 
!Step 1:    
 
|-
 
|-
|Since our interval is <math style="vertical-align: -5px">[0,3]</math> and we are using 3 rectangles, each rectangle has width 1. So, the left-hand Riemann sum is
+
|Since our interval is <math style="vertical-align: -5px">[0,3]</math> and we are using <math style="vertical-align: -1px">3</math> rectangles, each rectangle has width <math style="vertical-align: -1px">1.</math> So, the left-hand Riemann sum is
|-
 
| &nbsp;&nbsp; <math style="vertical-align: 0px">1(f(0)+f(1)+f(2))</math>
 
 
|-
 
|-
 
|
 
|
 +
::<math style="vertical-align: 0px">1(f(0)+f(1)+f(2)).</math> 
 
|}
 
|}
  
Line 35: Line 37:
 
|Thus, the left-hand Riemann sum is  
 
|Thus, the left-hand Riemann sum is  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -4px">1(f(0)+f(1)+f(2))=1+0+-3=-2</math>
+
| &nbsp;&nbsp; <math style="vertical-align: -4px">1(f(0)+f(1)+f(2))=1+0+-3=-2.</math>
 
|}
 
|}
  
Line 42: Line 44:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Since our interval is <math style="vertical-align: -5px">[0,3]</math> and we are using 3 rectangles, each rectangle has width 1. So, the right-hand Riemann sum is
+
|Since our interval is <math style="vertical-align: -5px">[0,3]</math> and we are using <math style="vertical-align: -1px">3</math> rectangles, each rectangle has width <math style="vertical-align: -1px">1.</math> So, the right-hand Riemann sum is
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -5px">1(f(1)+f(2)+f(3))</math>.  
+
|
 +
::<math style="vertical-align: -5px">1(f(1)+f(2)+f(3)).</math>   
 
|-
 
|-
 
|
 
|
Line 53: Line 56:
 
|Thus, the right-hand Riemann sum is  
 
|Thus, the right-hand Riemann sum is  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -5px">1(f(1)+f(2)+f(3))=0+-3+-8=-11</math>
+
|
 +
::<math style="vertical-align: -5px">1(f(1)+f(2)+f(3))=0+-3+-8=-11.</math>
 
|}
 
|}
  
Line 60: Line 64:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Let <math style="vertical-align: 0px">n</math> be the number of rectangles used in the right-hand Riemann sum for <math style="vertical-align: -5px">f(x)=1-x^2</math>.
+
|Let <math style="vertical-align: 0px">n</math> be the number of rectangles used in the right-hand Riemann sum for <math style="vertical-align: -5px">f(x)=1-x^2.</math>
 
|-
 
|-
|The width of each rectangle is <math style="vertical-align: -13px">\Delta x=\frac{3-0}{n}=\frac{3}{n}</math>.
+
|The width of each rectangle is  
|-
 
|
 
 
|-
 
|-
 
|
 
|
 +
::<math style="vertical-align: -13px">\Delta x=\frac{3-0}{n}=\frac{3}{n}.</math>
 
|}
 
|}
  
Line 74: Line 77:
 
|So, the right-hand Riemann sum is  
 
|So, the right-hand Riemann sum is  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -14px">\Delta x \bigg(f\bigg(1\cdot \frac{3}{n}\bigg)+f\bigg(2\cdot \frac{3}{n}\bigg)+f\bigg(3\cdot \frac{3}{n}\bigg)+\ldots +f(3)\bigg)</math>.
+
|
 +
::<math style="vertical-align: -14px">\Delta x \bigg(f\bigg(1\cdot \frac{3}{n}\bigg)+f\bigg(2\cdot \frac{3}{n}\bigg)+f\bigg(3\cdot \frac{3}{n}\bigg)+\ldots +f(3)\bigg).</math>
 
|-
 
|-
 
|Finally, we let <math style="vertical-align: 0px">n</math> go to infinity to get a limit.   
 
|Finally, we let <math style="vertical-align: 0px">n</math> go to infinity to get a limit.   
Line 80: Line 84:
 
|Thus, <math style="vertical-align: -14px">\int_0^3 f(x)~dx</math> is equal to
 
|Thus, <math style="vertical-align: -14px">\int_0^3 f(x)~dx</math> is equal to
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -21px">\lim_{n\to\infty} \frac{3}{n}\sum_{i=1}^{n}f\bigg(i\frac{3}{n}\bigg)\,=\,\lim_{n\to\infty} \frac{3}{n}\sum_{i=1}^{n}\bigg(1-\bigg(i\frac{3}{n}\bigg)^2\bigg)</math>&thinsp;.
+
|
 +
::<math style="vertical-align: -21px">\lim_{n\to\infty} \frac{3}{n}\sum_{i=1}^{n}f\bigg(i\frac{3}{n}\bigg)\,=\,\lim_{n\to\infty} \frac{3}{n}\sum_{i=1}^{n}\bigg(1-\bigg(i\frac{3}{n}\bigg)^2\bigg).</math>
 
|}
 
|}
  

Revision as of 13:22, 18 April 2016

Let .

a) Compute the left-hand Riemann sum approximation of with boxes.
b) Compute the right-hand Riemann sum approximation of with boxes.
c) Express as a limit of right-hand Riemann sums (as in the definition of the definite integral). Do not evaluate the limit.
Foundations:  
Recall:
1. The height of each rectangle in the left-hand Riemann sum is given by choosing the left endpoint of the interval.
2. The height of each rectangle in the right-hand Riemann sum is given by choosing the right endpoint of the interval.
3. See the page on Riemann Sums for more information.

Solution:

(a)

Step 1:  
Since our interval is and we are using rectangles, each rectangle has width So, the left-hand Riemann sum is
Step 2:  
Thus, the left-hand Riemann sum is
  

(b)

Step 1:  
Since our interval is and we are using rectangles, each rectangle has width So, the right-hand Riemann sum is
Step 2:  
Thus, the right-hand Riemann sum is

(c)

Step 1:  
Let be the number of rectangles used in the right-hand Riemann sum for
The width of each rectangle is
Step 2:  
So, the right-hand Riemann sum is
Finally, we let go to infinity to get a limit.
Thus, is equal to
Final Answer:  
(a)  
(b)  
(c)  

Return to Sample Exam